SELEKSI POHON PLUS TENGKAWANG TUNGKUL (Shorea stenoptera Burck) DI TEMBAWANG DESA PENYELADI KABUPATEN SANGGAU - Awaludin, M; Muin, Abdurrani; Suryantini, Rosa (Universitas Tanjungpura, 2018)
Tengkawang Tungkul is an endemic species of plant that grows in West Kalimantan which is the best quality wood. Adult tengkawang rooted with good or bad phenotypes will produce fruit and seeds that function as new plant seeds. Knowladge of the source of native seeds or mother trees is the most important part of getting the most quality seeds. The choice of trees as a plus tree is important to produce the best quality seeds. The purpose of this study was to determine the number of tengkawang tungkul that met the criteria as a Plus Tree in tembawang Penyeladi village. This research was conducted in the survey method to determine plus tree candidates and compare trees as a basis for determining plus trees. The object of this research is tengkawang tungkul tree with a diameter of >30 cm and flowering and producing fruit. The phenotype characters consist of a total of tree height, the height of free branches, stem diameter, outward bark width, and tree health. This research found that there were 8 tengkawang tungkul trees that have potential to of plus trees that meet the criteria of a plus tree. The highest score was 72 which was found in plus tree candidate no. 27, a total score of 71 for no. 6, and a totalÂ score of 63 which belongs to candidates numbers 1, 16, 19, 21, 31, and 36. Based on the calculation, the total scores show that a part of the mother trees of tengkawang tungkul in tembawang Penyeladi village of Sanggau regency have met the criteria to be made plus trees.Â Â Keywords: Mother-Trees, Phenotype Characters, Plus Tree, Tengkawang tungkul.